Penanaman dan Pelatihan Hidroponik sebagai Peluang Usaha di Kelurahan Pancoran RT 08/RW 03 Jakarta Selatan - Donant Alananto Iskandar; Ignatius Ario Sumbogo; Maulana Malik Muhammad (LPMP Imperium, 2025)
This initiative addresses the challenges of rapid population growth and limited land availability by offering a sustainable solution: hydroponic farming. The main goal of this service is to empower communities by equipping them with the knowledge and skills to grow hydroponic plants, a cultivation method that does not require large areas of land. By teaching hydroponic farming techniques, this service allows individuals to utilize limited space, transforming small plots of land or even indoor spaces into productive agricultural environments. This approach not only provides a practical solution to food production but also creates economic opportunities for individuals and families, as they can sell hydroponically grown products, such as vegetables or herbs, to local markets or directly to consumers. This community service was carried out on Saturday, December 21, 2024 at RW 3, Pancoran Village, South Jakarta, which was attended by local residents who were interested in the world of utilizing garden plants with the aim that at least the community is able to use their yard as a hobby, social activity and business.